KEMAMPUAN GOTONG ROYONG PESERTA DIDIK PADA PEMBELAJARAN P5 DI SDN 80/I MUARA BULIAN - Kemal Amrul Haq; Faizal Chan; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out the ability of students to work together in elementary school. This research was conducted at SDN 80/I muara bulian in February and March 2024. This research uses descriptive quantitative methods, researchers use cluster random sampling techniques consisting of 6 classes, with a total of 48 respondents. The results showed that the students' mutual cooperation ability had an average score of 20.7 (quite good) with the highest score of 28 (very good) and the lowest score of 12 (not good enough). Overall, the ability of mutual cooperation of students is quite good from 7 indicators of low enough students on social coordination. There are still many learners who do not understand their roles and responsibilities in the group. Based on these results, it can be concluded that the ability to get along with students in the research school is classified as quite good. This ability can be improved by maximising the use of P5 activities.